Analysis of physical development and the structure of disease in persons aged 45-59 years - V. A. Pogodina; A. I. Babenko; E. A. Babenko; A. V. Polovnikova (Acta Biomedica Scientifica, 2018)
Changes in the state of health of people of the older generation may not invest in age-sex ratios and reduce sanogenetic mechanism that determines the structure of the disease. With the help of sample population technique, using a representative, stratified sampling and analytical discussion we studied indicators of physical development and the characteristics of the disease in adults 45-59 years old according to the medical records for the years 2015-2016 in the city of Novosibirsk. Content of the study was data from the official statistical registration forms (N 025/u-04, N 025-12, N 131/a) of 300 patients 45-59 years. The analysis showed that the portion of individuals of the older age group with standard indicators such as body build, blood pressure, heart rate and respiratory movements, recognized in the Russian Federation made from 13.7 to 26.3 %. While adults of this age, with asthenic and hypersthenic body type, made respectively 28.3 and 56.3 %. The share of contingent having bradycardia accounted for 26.0 %, tachycardia - 52.3 %. The proportion of persons with low and high blood pressure level was 11.3 and 75.0 %, respectively. Patients with bradypnea were determined in 24.4 %, with tachypnea - 49.3 %. Among adults of 45-59 years, the most common disorders were noninflammatory diseases of female genital organs, diseases of male genital organs and dorsopathies. The contingent prevailed with a mild (55.0%) and severe (40.0%) degrees of severity of the disease, requiring a health check-up. The revealed changes in the health of the older generation will determine the relevance of diagnostic, curative and preventive measures taking into account regional peculiarities.